UTAUT Model Implementation On User Behavior In Use Of Information Technology - Aan Nehru Awanto; Yusaq Tomo Ardianto; Dwi Arman Prasetya (Universitas Merdeka Malang, 2020)
Purpose analyze and retest the technology use and acceptance model proposed by Venkatesh et al. (2003) where there are four main variables that affect user intention and user behavior in using information technology. Methodology this study uses a quantitative method, and data obtained using questionnaires. Sampling uses survey techniques with a total sample of 50 employees of the Tourism and Culture Office of Malang Regency. The analysis technique in processing data uses the SPSS program. Research findings this study shows that in the technology acceptance model, user intention and user behavior can be influenced by four variables such as performance, effort, social influence, and supporting conditions. DOI: https://doi.org/10.26905/jtmi.v6i1.4156